STRATEGI KOMUNIKASI PEMERINTAH DAERAH DALAM MENSOSIALISASIKAN INFORMASI PUBLIK DI KABUPATEN ACEH BARAT - Febriani , Diah Lastri; Juliani, Reni (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
Information is everyone's need, and the right to obtain information is a human right, Law Number 14 of 2008 provides a legal basis for everyone to have the right to obtain public information. PPID plays an important role in service and provision of information, PPID must carry out its role and communication strategy effectively and efficiently in order to realize the implementation of UU KIP. This study uses the Laswell communication model, with field research methods, and qualitative descriptive analysis, interview data collection techniques, observations and complementary data. The research was carried out at the Communication, Information and Encryption Office of West Aceh Regency, specifically the Documentation Information Management Officer (PPID), who appointed 2 informants, namely the head of the Public Communications Division and the Head of the PPID Section. The results of this research explain that the West Aceh District Communication, Information and Encryption Service, which is the Main PPID, has its role in accordance with Law Number 14 of 2008, PPID has carried out its duties, functions and steps in accordance with the requirements of the KIP Law, and regarding operations and the mechanism of Information Services is quite good and satisfactory and facilitates the community. PPID has implemented its communication strategy in socializing to the community by forming the Gampong Information Group (KIG), which is very useful for the community in terms of information services.